Adaptation to a New Tuning Standard in a Musician with Tone-color Synesthesia and Absolute Pitch. Issue 3 (2nd July 2020) - Lebeau, Cathy; Tremblay, Marie Nadeau; Richer, François
ABSTRACT: Developmental synesthesia is a neurological condition in which certain perceptions or cognitions trigger atypical supplementary perceptions (e.g., tones evoke specific colors). Tone-color synesthesia is prevalent in musicians and is associated with enhanced music processing and increased connectivity in auditory cortex. We report the case of NTM, a professional violinist with tone-color synesthesia as well as absolute pitch. When she switched from modern (A440 tuning standard) to baroque (A415 tuning standard) interpretation, NTM experienced a serious incongruence in her synesthesia and absolute pitch which severely interfered with her musical performance. However, through explicit self-training over months using color cues from her synesthesia, she learned new pitch associations for her note concepts which canceled this interference. This ability was validated through a second evaluation four years after the initial evaluation. NTM can now switch between both standards with little interference. She also reported changes in her non-musical synesthesia and developed new synesthesia to a tonal language (mandarin). This case indicates that synesthetic associations can be used as anchors to learn a new tuning standard when interference is high. It also suggests that tone concepts can undergo important perceptual modifications and still maintain their stability as inducers of synesthesia.